Insights into Clinical Characteristics and Management Strategies: A Case Series of Granulosa Cell Tumors - Gupta, Sumedha; Kalwaniya, Dheer Singh; Mishra, Archana (Asian Pacific Journal of Cancer Care, 2025)
Background: Granulosa cell tumors (GCTs) are rare neoplasms with predominantly low malignant potential, primarily affecting peri-menopausal individuals. This case series investigates six patients diagnosed with GCT, emphasizing clinical features, prognostic markers, and treatment strategies. Methods: This retrospective analysis focuses on patients diagnosed with GCT at Safdarjung Hospital between June 2022 and June 2023. Data collection included demographics, clinical presentations, diagnostic findings, treatment modalities, and follow-up outcomes. Results: The case series comprised various presentations, ranging from asymptomatic masses to complications such as ovarian torsion and tumor rupture. Most patients presented with hormonally active tumors, predominantly producing estrogen. Surgical management, including unilateral salpingo-oophorectomy or total abdominal hysterectomy with bilateral salpingo-oophorectomy, was the primary treatment modality. Prognostic factors such as tumor size, stage, and mitotic index were identified, guiding clinical decision-making. Close surveillance post-surgery was essential due to the potential for late recurrences. Conclusion: This case series enhances understanding of ovarian GCTs, providing insights into their clinical management and prognosis. Early detection, prognostic marker assessment, and vigilant surveillance are crucial for optimizing patient outcomes